The aqueous extract of Triumfetta semitriloba (Tiliaceae) does not inhibit the in-vitro hydrolytic activity of the major pancreatic enzymes - Arce-Urbina, María Elena (2003)
The aqueous extract of Triumfetta semitriloba is part of the Costa Rican folk pharmacopoeia. It shows no in-vitro inhibitory action on the hydrolytic activity of porcine pancreatic amylase, lipase or proteases, thus diminishing the concern of intestinal malabsorption in human beings.